CONSEQUENCES OF A PROGRAM DIRECTED TO HEALTH, APPLIED IN PHYSICAL EDUCATION, ON ANTHROPOMETRIC MEASURES OF STUDENTS (Fiep Bulletin - online, 2014)
The objective of this study was to investigate what the consequences of a program directed to education in health, developed in physical education, on anthropometric measures of students. This is an experimental study with students from 13 to 16 years (14.03± 0.93), of both genders, in the city of Teresina/Brazil. The sample was composed of 373 students (184 school study and 189 school control). The measures assessed were: body mass (MC), stature (AND), triceps skinfold (TSF) and subscapular (DCS). The intervention occurred in the study group and consisted in a program for physical education with content organized in a) conceptual dimensions: concepts related to health and b) attitudinal aspects: motivation of attitudes that aimed to modify negative behavior of health. In the control group the contents were addressed on physical fitness and sports. The statistical treatment used the test Split-plot ANOVA with post hoc comparisons Sheffer for intragroup and intergroup. The level of significance was p
Keywords: Program of health education; physical education